ANALYSIS OF THE BOOK MARI BELAJAR BAHASA ARAB BASED ON W.F. MACKEY’S THEORY AND THE PRINCIPLES OF DEEP LEARNING - Risma Pebriyani; Yusuf Ali Tantowi (SOSIOEDUKASI, 2026)
This study analyzes the textbook Mari Belajar Bahasa Arab by Drs. H. Maman Abdul Djaliel, M.Ag., based on W.F. Mackey’s theory and the principles of Deep Learning, with a focus on the content and presentation for first-grade students at the Madrasah Diniyah Takmiliyah Ula (MDTU). This study employs a qualitative approach with a content analysis design, using the textbook as the primary data and scientific literature as supporting data. Data were collected through documentation and literature review, utilizing instruments based on the four aspects of Mackey’s theory (selection, gradation, presentation, repetition) and the three principles of Deep Learning (mindful, meaningful, and joyful learning). Analysis was conducted through the stages of data reduction, presentation, and verification. The results indicate that the textbook meets all four aspects of Mackey’s theory: content aligned with the curriculum and student characteristics; gradation from simple to complex concepts; presentation using differential, ostensive, illustrated, and contextual procedures; and repetition through the reuse of vocabulary and sentence patterns across chapters. From a Deep Learning perspective, the principles of mindful and meaningful learning are achieved through contextual, integrated content. Although the textbook is structurally sound, it does not fully support joyful learning because it lacks diverse activities, visual appeal, and opportunities for feedback and self-reflection. Therefore, textbook evaluations should consider both structural features and the overall quality of the student learning experience.